Mechanisms of Pathogenic Candida Species to Evade the Host Complement Attack - Singh, Dhirendra Kumar; Tóth, Renáta; Gácser, Attila (Frontiers in Cellular and Infection Microbiology, 2020)
Members of Candida species are common colonizers of the human skin, mucosal surfaces, vagina, and the gut. As human commensals, Candida species do not cause any notable damage in healthy individuals; however, in certain condition they can initiate a wide range of diseases such as chronic disseminated candidiasis, endocarditis, vaginitis, meningitis, and endophthalmitis. The incidence of Candida infections has increased worldwide, with mortality rates exceeding 70% in certain patient populations. Approximately 95% of infections are caused by six species: C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. krusei, and C. auris. Interestingly, the host immune response against these closely related fungi varies. Complement proteins are important components of the innate immune system as they represent a crucial part of host defense, protecting the host by lysing pathogens or by increasing their phagocytosis by lymphocytes through opsonization. This review summarizes interactions of host complement proteins with pathogenic Candida species, including C. albicans as well as non- albicans Candida species such as C. parapsilosis. We will highlight the various ways complement is activated by Candida species, describe the antifungal effects of complement cascades and explore the mechanisms adopted by members of pathogenic Candida species for evading complement attack.